2022
DOI: 10.1167/tvst.11.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pupil Offset in Young Asian Adults With Mild-Moderate and High Myopia

Abstract: Purpose The purpose of this study was to explore the characteristics of pupil offset in young Asian adults with myopia. Methods In total, 1200 eyes (600 young adults, 18–35 years old) were divided into mild-moderate and high groups according to equivalent spherical diopters (SEQ). The pupil offset and its X and Y components were compared between the groups. Linear correlation was analyzed among pupil offset, X and Y components, and SEQ. Multiple linear regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…We found that pupil offset was linearly and positively correlated with preoperative MRSE in this study, which was consistent with a previous study (21). Furthermore, If the pupil offset was > 0.20 mm, there was a statistically signi cant correlation between pupil offset and MRSE.…”
Section: Discussionsupporting
confidence: 92%
“…We found that pupil offset was linearly and positively correlated with preoperative MRSE in this study, which was consistent with a previous study (21). Furthermore, If the pupil offset was > 0.20 mm, there was a statistically signi cant correlation between pupil offset and MRSE.…”
Section: Discussionsupporting
confidence: 92%